A siloxane PC composite material resistant to xenon lamp discoloration and a preparation method and application thereof

By optimizing the PC resin formulation and preparation process, a siloxane PC composite material resistant to xenon lamp aging and discoloration was prepared, solving the problem of insufficient weather resistance of polycarbonate resin in outdoor use and achieving long-term color stability and performance improvement of the material.

CN121182173BActive Publication Date: 2026-11-06GUANGDONG GREAT MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511567461.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-11-06
Estimated Expiration
2045-10-30

AI Technical Summary

Technical Problem

Polycarbonate resin is susceptible to the effects of ultraviolet rays, high temperature, and humidity during long-term outdoor use, which can lead to yellowing and a decline in mechanical properties. Existing modification methods are difficult to achieve long-term stable protective effects in high temperature and high humidity environments and may sacrifice other properties of the material.

Method used

A siloxane PC composite material resistant to xenon lamp aging and discoloration was prepared by rationally proportioning PC resin, siloxane PC resin, antioxidant, UV absorber, flame retardant, and colorant. High-speed mixing and melt blending extrusion processes were used to ensure uniform dispersion of each component, thereby improving the material's anti-aging and discoloration performance, color stability, mechanical properties, and thermal stability.

Benefits of technology

The prepared composite material maintains color stability during long-term outdoor use and possesses excellent mechanical properties, low-temperature resistance, and thermal stability, meeting the long-term use requirements of new energy vehicle parts and household appliance housings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a siloxane PC composite material resisting xenon lamp aging discoloration and a preparation method and application thereof, and raw materials for preparing the siloxane PC composite material resisting xenon lamp aging discoloration include the following components in percentage by weight 100%: PC resin 50-60%, siloxane PC resin 20-30%, antioxidant 2-5%, ultraviolet absorber 4-8%, flame retardant 2-8%, and toner 2-5%. The siloxane PC composite material resisting xenon lamp aging discoloration prepared by the application can be applied to housings of household appliances, new energy automobile accessories and the like, can be applied outdoors for a long time, can keep color stable, and has excellent mechanical properties, low-temperature resistance and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite materials, and in particular to a siloxane PC composite material resistant to xenon lamp aging and discoloration, its preparation method, and its application. Background Technology

[0002] Polycarbonate (PC) resin possesses excellent mechanical properties, transparency, and dimensional stability, making it widely used in electronics, automotive, and other industries. However, PC resin suffers from poor weather resistance. During long-term outdoor use, it is susceptible to photo-oxidative degradation due to environmental factors such as ultraviolet radiation, high temperatures, and humidity. This leads to yellowing, decreased mechanical properties, and severely impacts product appearance and lifespan. Particularly in applications such as new energy vehicle components and household appliance housings, materials not only need good mechanical properties but also must maintain color stability under long-term outdoor conditions to meet the aesthetic and functional requirements of the products.

[0003] To improve the weather resistance of PC resin, existing technologies typically employ the addition of additives such as UV absorbers and antioxidants. However, the effect of a single additive is limited, and it is difficult to achieve long-term stable protective effects in complex outdoor environments such as high temperature and high humidity. Furthermore, while some modification methods can improve weather resistance, they sacrifice other properties of the material, such as low-temperature toughness and flame retardancy, failing to meet the needs of practical applications.

[0004] Therefore, developing a PC-based composite material with excellent comprehensive performance that can effectively resist xenon lamp aging and discoloration is of great significance for expanding the application of PC resin in outdoor fields. Summary of the Invention

[0005] Purpose of the invention: The purpose of this invention is to provide a siloxane PC composite material resistant to xenon lamp aging and discoloration. Through reasonable raw material formulation design, the composite material possesses excellent resistance to xenon lamp aging and discoloration, good color stability, mechanical properties, low-temperature resistance, and thermal stability, meeting the requirements for long-term outdoor use. At the same time, this invention provides a preparation method and application of the composite material, solving the problems of insufficient weather resistance of existing PC materials in outdoor applications.

[0006] The technical solution of this invention: The present invention discloses a siloxane PC composite material resistant to xenon lamp aging and discoloration, characterized in that the raw materials for preparing the siloxane PC composite material are 100% by weight and include the following components: 50-60% PC resin, 20-30% siloxane PC resin, 2-5% antioxidant, 4-8% ultraviolet absorber, 2-8% flame retardant, and 2-5% colorant.

[0007] Furthermore, the PC resin is bisphenol A type polycarbonate with a weight-average molecular weight of 20,000-35,000 g / mol.

[0008] Furthermore, the siloxane PC resin is a copolymer of bisphenol A type polycarbonate and cage-like polysilsesquioxane.

[0009] Furthermore, the preparation of the siloxane PC resin includes the following steps: S1: Weigh out bisphenol A type polycarbonate and cage-shaped polysilsesquioxane separately, and set aside; S2: Add the bisphenol A type polycarbonate weighed in step S1 to a high-speed mixer, spray the chain extender while stirring at 800-1000r / min, mix at 80-100℃ for 5-10 minutes, then add the cage-shaped polysilsesquioxane weighed in step S1, and continue mixing for 10-15 minutes. S3: Add the mixture from step S2 into the reactor, add the catalyst, slowly raise the temperature to 220-240℃, and perform polycondensation reaction for 4-5 hours under vacuum conditions <10Pa; S4: Then, the polycondensation product from step S3 is extruded using a co-rotating twin-screw extruder with an aspect ratio ≥40, a rotation speed of 300-350 r / min, and a temperature of 250-255°C. After cooling and pelletizing, the pellets are vacuum dried at 100-120°C for 4-6 hours to obtain the siloxane PC resin.

[0010] Furthermore, the cage-like polysilsesquioxane is one or more of N-phenylamino-cage-like polysilsesquioxane, trisilylphenyl-cage-like polysilsesquioxane, and acrylic-cage-like polysilsesquioxane; the amount of cage-like polysilsesquioxane added is 5-8% of the mass of bisphenol A type polycarbonate.

[0011] Furthermore, the chain extender is isophorone diisocyanate; the amount of isophorone diisocyanate added is 0.5-1% of the mass of bisphenol A polycarbonate.

[0012] Furthermore, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168; the ultraviolet absorber is one or more of UV-531 and UV-326.

[0013] Furthermore, the flame retardant is one or more of melamine cyanurate and triphenyl phosphate; the colorant is one or more of organic pigments and inorganic pigments.

[0014] This invention also provides a method for preparing a siloxane PC composite material resistant to xenon lamp aging and discoloration, characterized by comprising the following steps: (1) Weigh out the PC resin, siloxane PC resin, antioxidant, UV absorber, flame retardant and colorant according to the above weight percentages; (2) Add the weighed PC resin, siloxane PC resin, antioxidant, UV absorber, flame retardant and color powder to a high-speed mixer and mix at 80-100℃ for 5-10 minutes to ensure that the components are fully dispersed and uniform. (3) The uniformly mixed material is added to a twin-screw extruder for melt blending and extrusion. The temperature of the twin-screw extruder is set to 220-260℃ and the screw speed is 200-300r / min. The material is extruded, water-cooled and pelletized to obtain a siloxane PC composite material resistant to xenon lamp aging and discoloration.

[0015] The siloxane PC composite material with anti-xenon lamp aging and discoloration provided by this invention can be used in household appliance housings, new energy vehicle parts, etc.

[0016] Beneficial effects: The siloxane PC composite material prepared by this invention is resistant to xenon lamp aging and discoloration. It can be used in the shells of household appliances and new energy vehicle parts, meeting the requirements for long-term outdoor use. It can maintain excellent color stability during long-term outdoor use and has excellent mechanical properties, low-temperature resistance, and thermal stability. Detailed Implementation

[0017] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.

[0018] Unless otherwise specified, all chemical reagents used in this invention are commercially available analytical grade reagents.

[0019] N-Phenylan-cage polysilsesquioxane, CAS No.: 1708993-28-5, Trisilyl phenyl-cage polysilsesquioxane, CAS No.: 444315-26-8, Acrylic-cage polysilsesquioxane, CAS No.: 1620202-27-8 were purchased from Forsman Technology (Beijing) Co., Ltd.

[0020] The preparation of siloxane PC resin A includes the following steps: S1: Weigh out 1000g of bisphenol A type polycarbonate (Mw=30000g / mol) and 50g of N-phenylamino-cage polysilsesquioxane for later use; S2: Add the bisphenol A type polycarbonate weighed in step S1 to a high-speed mixer, spray 5g of isophorone diisocyanate while stirring at 1000r / min, mix at 100℃ for 5 minutes, then add the N-phenylamino-cage polysilsesquioxane weighed in step S1, and continue mixing for 10 minutes. S3: Add the mixture from step S2 into the reactor, add 0.5g of stannous octoate, slowly raise the temperature to 240℃, and perform polycondensation reaction under vacuum of 8Pa for 5h; S4: Then, the polycondensation product from step S3 is extruded using a co-rotating twin-screw extruder with a length-to-diameter ratio of 38, a rotation speed of 350 r / min, and a temperature of 250°C. After cooling and pelletizing, the pellets are vacuum dried at 120°C for 4 hours to obtain the siloxane PC resin A.

[0021] Preparation of siloxane PC resin B: The difference between this preparation and the preparation of siloxane PC resin A is that 50g of N-phenylamino-cage polysilsesquioxane is replaced with 80g of trisilyl alcohol phenyl-cage polysilsesquioxane.

[0022] Preparation of siloxane PC resin C: The difference between this preparation and the preparation of siloxane PC resin A is that 50g of N-phenylamino-cage polysilsesquioxane is replaced with 30g of trisilyl alcohol phenyl-cage polysilsesquioxane and 30g of acrylic-cage polysilsesquioxane.

[0023] Example 1: A method for preparing siloxane PC composite materials, characterized by comprising the following steps: (1) Weigh 6 kg of PC resin (Mw=28000 g / mol), 2.5 kg of siloxane PC resin A, 0.3 kg of antioxidant 1010, 0.5 kg of UV-531, 0.4 kg of melamine cyanurate and 0.3 kg of titanium dioxide; (2) Weigh 6 kg of PC resin (Mw=28000 g / mol), 2.5 kg of siloxane PC resin A, 0.3 kg of antioxidant 1010, 0.5 kg of UV-531, 0.4 kg of melamine cyanurate and 0.3 kg of titanium dioxide and add them to a high-speed mixer. Mix at 100°C for 10 min to ensure that the components are fully dispersed and uniform. (3) The uniformly mixed material is added to a twin-screw extruder for melt blending and extrusion. The temperature of the twin-screw extruder is set to 250℃ and the screw speed is 300r / min. The material is extruded, water-cooled and pelletized to obtain a siloxane PC composite material resistant to xenon lamp aging and discoloration.

[0024] Example 2: The difference between this preparation and Example 1 is that 6 kg of PC resin (Mw=28,000), 2.5 kg of siloxane PC resin B, 0.3 kg of antioxidant 1010, 0.5 kg of UV-531, 0.4 kg of melamine cyanurate and 0.3 kg of titanium dioxide are replaced with 5.5 kg of PC resin (Mw=35000 g / mol), 3 kg of siloxane PC resin A, 0.4 kg of antioxidant 1010, 0.6 kg of UV-531, 0.3 kg of melamine cyanurate and 0.2 kg of titanium dioxide; Example 3: The difference between this preparation and Example 1 is that 6 kg of PC resin (Mw=28,000), 2.5 kg of siloxane PC resin C, 0.3 kg of antioxidant 1010, 0.5 kg of UV-531, 0.4 kg of melamine cyanurate and 0.3 kg of titanium dioxide are replaced with 5.8 kg of PC resin (Mw=20000 g / mol), 2.2 kg of siloxane PC resin C, 0.2 kg of antioxidant 1010, 0.4 kg of UV-531, 0.8 kg of melamine cyanurate and 0.6 kg of titanium dioxide. Comparative Example 1: The difference between this preparation and Example 1 is that 2.5 kg of siloxane PC resin A is replaced with 2.5 kg of PC resin (Mw = 28000 g / mol).

[0025] Comparative Example 2: The difference between this preparation and Example 1 is that 2.5 kg of siloxane PC resin A is replaced with 2.5 kg of polydimethylsiloxane.

[0026] The siloxane PC composite materials resistant to xenon lamp aging and discoloration prepared in Examples 1-3 and Comparative Examples 1-2 were fabricated into rectangular specimens of 80mm × 10mm × 4mm for testing of anti-aging properties, mechanical properties (notched impact strength), low-temperature resistance, and thermal stability. 1. UV Aging Resistance Test: According to the standards ASTM G155-18 "Standard Implementation Procedure for the Operation of Xenon Arc Lamp Equipment for Exposure of Nonmetallic Materials" and ISO 4892-2:2013 "Laboratory Light Sources for Plastics - Exposure Tests - Part 2: Xenon Arc Lamps", the xenon lamp aging test was conducted. At a wavelength of 340 nm, the irradiance was controlled at 1.2 kW / m² to simulate the ultraviolet radiation intensity in outdoor sunlight. The blackboard temperature was set at 65±3℃, and the relative humidity was maintained at 50±5%. The aging was carried out for 1000 hours, and the color change of the samples before and after aging was measured using a colorimeter.

[0027] 2. Mechanical Properties: Following ISO 179-1:2010 "Determination of impact properties of simply supported beams of plastics - Part 1: Non-instrumental impact testing", the material's ability to resist failure under high-speed impact loads was tested. The composite material was injection molded into standard specimens of 80mm × 10mm × 4mm, using a type A notch (notch thickness remaining 8mm, notch angle 45°, bottom radius 0.25mm). A pendulum impact testing machine was used, with a pendulum energy of 10J and a speed set to 3.8m / s. The test was conducted in a standard laboratory environment (temperature 23±2℃, relative humidity 50±5%). Each group of specimens was tested 5 times, and the average value was taken as the result.

[0028] 3. Low-temperature resistance: According to ISO 179-3:2010 "Determination of impact properties of simply supported beams of plastics - Part 3: Tests at low temperatures" and GB / T 1682-2019 "Determination of low-temperature brittleness of vulcanized rubber (single specimen method)", the toughness of the material in low-temperature environment is evaluated. The specimen is placed in a -40℃ low-temperature environment chamber for 4 hours, and the specimen is quickly removed. The impact test is completed within 10 seconds. The pendulum energy, impact velocity and other parameters are consistent with the room temperature notched impact test. Each group of specimens is tested 5 times, and the results are recorded and analyzed.

[0029] 4. According to ISO 75-2:2013 "Determination of temperature of deformation under load on plastics - Part 2: Test method under flexural stress conditions", the temperature at which the bending deformation of the specimen reaches the specified value under specified load and constant rate of heating is determined to characterize the heat resistance of the material. A heat distortion Vicat softening point tester (Chengde Jinjian XHRD-300A) is used to bring the surface stress of the specimen to 1.8 MPa, and the temperature is increased at a constant rate of 120℃ / h. When the bending deformation at the midpoint of the specimen reaches 0.21 mm, the temperature at this point is recorded as the heat distortion temperature (HDT). Each group of specimens is tested three times, and the average value is taken.

[0030] Table 1: Test Results Table As can be seen from the above data, the test results of the examples and comparative examples show that the anti-xenon lamp aging discoloration siloxane PC composite materials prepared by the present invention (Examples 1-3) are significantly better than Comparative Example 1 (without siloxane PC resin) and Comparative Example 2 (with polydimethylsiloxane) in terms of anti-aging properties, mechanical properties, low temperature resistance and thermal stability. This fully verifies the effectiveness of the formulation and preparation method of the present invention. The obtained composite material can meet the stringent requirements of long-term outdoor use and has broad application prospects in the fields of new energy vehicle parts and household appliance housings.

[0031] This invention can also be implemented in various other ways. Without departing from the spirit and essence of this invention, those skilled in the art can make various corresponding changes and modifications according to this invention, but these corresponding changes and modifications should all fall within the protection scope of the appended claims.

Claims

1. A siloxane PC composite resistant to discoloration from xenon lamp aging, characterized in that, The raw materials for preparing the xenon lamp aging-resistant siloxane PC composite material, by weight percentage, comprise the following components: 50-60% PC resin, 20-30% siloxane PC resin, 2-5% antioxidant, 4-8% UV absorber, 2-8% flame retardant, and 2-5% colorant; Preparation of the siloxane PC resin, Includes the following steps: S1: Weigh out bisphenol A type polycarbonate and cage-shaped polysilsesquioxane separately, and set aside; S2: Add the bisphenol A type polycarbonate weighed in step S1 to a high-speed mixer, spray the chain extender while stirring at 800-1000r / min, mix at 80-100℃ for 5-10 minutes, then add the cage-shaped polysilsesquioxane weighed in step S1, and continue mixing for 10-15 minutes. S3: Add the mixture from step S2 into the reactor, add the catalyst, slowly raise the temperature to 220-240℃, and perform polycondensation reaction for 4-5 hours under vacuum conditions <10Pa; S4: Then, the polycondensation product from step S3 is extruded using a co-rotating twin-screw extruder with an aspect ratio ≥40, a rotation speed of 300-350 r / min, and a temperature of 250-255°C. After cooling and pelletizing, the pellets are vacuum dried at 100-120°C for 4-6 hours to obtain the siloxane PC resin. A method for preparing a siloxane PC composite material resistant to xenon lamp aging and discoloration includes the following steps: (1) Weigh out the PC resin, siloxane PC resin, antioxidant, UV absorber, flame retardant and colorant according to the above weight percentages; (2) Add the weighed PC resin, siloxane PC resin, antioxidant, UV absorber, flame retardant and color powder to a high-speed mixer and mix at 80-100℃ for 5-10 minutes to ensure that the components are fully dispersed and uniform. (3) The uniformly mixed material is added to a twin-screw extruder for melt blending and extrusion. The temperature of the twin-screw extruder is set to 220-260℃ and the screw speed is 200-300r / min. The material is extruded, water-cooled and pelletized to obtain a siloxane PC composite material resistant to xenon lamp aging and discoloration.

2. The siloxane PC composite material resistant to xenon lamp aging and discoloration according to claim 1, characterized in that, The PC resin is bisphenol A type polycarbonate with a weight-average molecular weight of 20,000-35,000 g / mol.

3. The siloxane PC composite material resistant to xenon lamp aging and discoloration according to claim 1, characterized in that, The siloxane PC resin is a copolymer of bisphenol A type polycarbonate and cage-shaped polysilsesquioxane.

4. The siloxane PC composite material resistant to xenon lamp aging and discoloration according to claim 1, characterized in that, The cage-like polysilsesquioxane is one or more of N-phenylamino-cage-like polysilsesquioxane, trisilylphenyl-cage-like polysilsesquioxane, and acrylic-cage-like polysilsesquioxane; the amount of cage-like polysilsesquioxane added is 5-8% of the mass of bisphenol A polycarbonate.

5. The siloxane PC composite material resistant to xenon lamp aging and discoloration according to claim 1, characterized in that, The chain extender is isophorone diisocyanate; the amount of isophorone diisocyanate added is 0.5-1% of the mass of bisphenol A polycarbonate.

6. The siloxane PC composite material resistant to xenon lamp aging and discoloration according to claim 1, characterized in that, The antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168; the ultraviolet absorber is one or more of UV-531 and UV-326.

7. The siloxane PC composite material resistant to xenon lamp aging and discoloration according to claim 1, characterized in that, The flame retardant is one or more of melamine cyanurate and triphenyl phosphate; the colorant is one or more of organic pigments and inorganic pigments.

8. The application of the anti-xenon lamp aging and discoloration siloxane PC composite material according to any one of claims 1-7 in the housings of household appliances and new energy vehicle parts.

Citation Information

Patent Citations

  • Transparent flame-retardant PC composite material and preparation method thereof

    CN105924922A

  • Halogen-free and flame-retardant PC material capable of resisting long-term heat aging, and preparation method thereof

    CN109971149A